POLITENESS PRACTICES IN BUGIS SOCIETY - Mahmud, Murni (Kajian Linguistik dan Sastra, 2011)
This paper discusses politeness practices as one of the important cultural normsin Bugis society. The main focus is to see the factors influencing Bugis practices ofpoliteness such as social status, age, gender, and familiarity. This paper is a part ofmy study on politeness in Bugis society, conducted in 2005 in two different Bugiscommunities in South Sulawesi: the first was in Awangpone, a rural area a fewkilometres north of the regional peninsula of South Sulawesi; the second was inParepare, the second city of the province located on the west coast, about 155 kmnorth of Makassar. The result of the research shows the significant influence ofthose above factors in the practices of Bugis politeness. There is a high tendency toact and speak with a high degree of politeness to signify their high status. However,other factors such as age, gender, and familiarity counteract each other to performhigh level of politeness of Bugis people.Key words: Politeness, Social Status, Age, Gender, Familiarity, Bugis Society